Factors Affecting on Purchasing Decision Online Food and Beverages through Gofood - Tafsirudin Tafsirudin; Dewi Fatmasari; Moh. Mab'ruri Faozi (Cirebon International Journal of Economics and Business, 2023)
This study investigates the individual and joint influence of product quality, service quality, and consumer trust quality on online food and beverage purchasing decisions through Gofood, employing a quantitative approach. Drawing upon a population of 734 Islamic economics students, the Slovin formula yielded a sample of 90 respondents. Data collection utilized a questionnaire and analysis involved data quality assessment, classical assumption testing, multiple linear regression, and hypothesis testing using IBM SPSS 22. Findings reveal that all three independent variables, (X1) product quality, (X2) service quality, and (X3) trust quality, exert a simultaneous and significant influence on the dependent variable, (Y) purchasing decisions. This conclusion is supported by both the F-test (Fcount = 67.779 > Ftable = 3.17, p < 0.05) and individual t-tests demonstrating significant individual effects for each variable. Therefore, the study confirms that product quality, service quality, and trust quality all play independent and collective roles in shaping online food and beverage purchasing decisions through Gofood.